2017
DOI: 10.1530/rep-17-0292
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of interferon-tau

Abstract: Thirty years ago, a novel type I interferon (IFN) was identified by molecular cloning of cDNA libraries constructed from RNA extracted from ovine and bovine pre-implantation embryos. This protein was eventually designated as IFN-tau (IFNT) to highlight its trophoblast-dependent expression. IFNT function is not immune related. Instead, it interacts with the maternal system to initiate the establishment and maintenance of pregnancy. This activity is indispensable for the continuation of pregnancy. Our review wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 81 publications
0
25
0
1
Order By: Relevance
“…Additionally, production of IFNT is exceptionally high over the few days. As pointed out in the accompanying chapter of Ealy and Woolridge (Ealy and Woolridge 2017), the relatively recent evolution of the IFNT genes required the acquisition of distinctive regulatory sequences upstream of their transcription start sites. Although the topic of transcriptional control of IFNT expression has been reviewed previously (Ealy and Yang 2009, Roberts 2007, Roberts, et al 2008), the review presented here is more comprehensive than the earlier ones.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, production of IFNT is exceptionally high over the few days. As pointed out in the accompanying chapter of Ealy and Woolridge (Ealy and Woolridge 2017), the relatively recent evolution of the IFNT genes required the acquisition of distinctive regulatory sequences upstream of their transcription start sites. Although the topic of transcriptional control of IFNT expression has been reviewed previously (Ealy and Yang 2009, Roberts 2007, Roberts, et al 2008), the review presented here is more comprehensive than the earlier ones.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have determined IFN gene evolution across 120 animal genomes that are available in current genome resources, and shown evolutionary significance and gene expansion of IFN genes in several representative species of amphibians, bats, and ungulates. Further using the porcine and bovine IFN complexes as a model, we have determined the molecular and functional diversity of the evolving IFN subtypes, particularly the less-studied unconventional IFN-ω subtype, which is an IFN subtype emerging after reptiles and expanding in bats and ungulates (715).…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of the IFN complex and IFN-ω diversity in bats and ungulates represent signature events of type I IFN evolution (715). We hypothesize that this subtype-expansion confers functional diversification that is necessary in regulating immune responses against species-specific and even cross-species viral infections (2, 715).…”
Section: Introductionmentioning
confidence: 99%
“…Another study identified 118 differentially expressed genes in the caruncular regions of the endometrium at day 20 of gestation between IVP and in vivo-generated pregnancies (Mansouri-Attia et al, 2009). One conceptus-secreted molecule that may be involved with some of this differential endometrial gene expression is interferon-tau (IFNT), the maternal recognition of pregnancy hormone in cattle (Spencer et al, 2016;Ealy and Wooldridge, 2017;Forde and Lonergan, 2017). Reports are equivocal about whether IFNT mRNA and protein abundance differ between IVP and in vivo-derived blastocysts and elongated conceptuses (Stojkovic et al, 1995;Kubisch et al, 2001;Bertolini et al, 2002a;Arnold et al, 2006).…”
Section: Peri-attachment Conceptusmentioning
confidence: 99%